Silver surfer omnibus - Slott, Dan 1967-; Allred, Michael (Marvel Worldwide, Inc., 2018)
For years he has soared the spaceways, exploring the length and breadth of the cosmos, experiencing everything it has to offer. But now the Silver Surfer's about to meet someone who will change his life forever: Earth girl Dawn Greenwood. And traveling with her, he will see it all through fresh eyes! Dan Slott (Amazing Spider-Man) and Michael Allred (Madman) take the Surfer, his new companion and his board "Toomie" on a wild ride to the very edge of the Marvel Universe -- and beyond! Their Eisner Award-winning run is destined to be remembered as an all-time-and-space classic!
Contains material originally published in magazine form as SILVER SURFER #1-15, ALL-NEW MARVEL NOW! POINT ONE #1 and SILVER SURFER #1 - 14
Keywords: Silver Surfer -- Fiktive Gestalt; Freundschaft; Weltall; Comic